1987
DOI: 10.1002/1097-0142(19870201)59:3+<605::aid-cncr2820591305>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Interferon in the treatment of hairy cell leukemia

Abstract: An ongoing multicenter study has confirmed earlier observations that interferon alfa-2b (Intron A, Schering Corp., Kenilworth, NJ) is effective in the treatment of hairy cell leukemia (HCL). The 212 evaluable subjects in this trial received 2 X 10(6) U/m2 of interferon alfa-2b subcutaneously, on an outpatient basis, three times a week for 1 year. Of this group, 166 had previously undergone splenectomy, and 94 had received chemotherapy; 96% had more than 50% hairy cells in the bone marrow. Objective responses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In 1984 Quesada et a1 first reported that monotherapy with partially purified natural leucocyte IFN-a was able to induce remissions in HCL (11). This report was subsequently corroborated in larger studies establishing IFN as the gold standard for HCL treatment (12,(160)(161)(162)(163)(164)(165)(166)(167)(168)(169)(170)(171). The different IFN species were used in doses of 10 -20 x lo6 IU/week divided into 3 or 7 doses administered either by s.c or i.m.…”
Section: Ifn Treatment Of Hclmentioning
confidence: 68%
See 2 more Smart Citations
“…In 1984 Quesada et a1 first reported that monotherapy with partially purified natural leucocyte IFN-a was able to induce remissions in HCL (11). This report was subsequently corroborated in larger studies establishing IFN as the gold standard for HCL treatment (12,(160)(161)(162)(163)(164)(165)(166)(167)(168)(169)(170)(171). The different IFN species were used in doses of 10 -20 x lo6 IU/week divided into 3 or 7 doses administered either by s.c or i.m.…”
Section: Ifn Treatment Of Hclmentioning
confidence: 68%
“…injections often on an outpatient basis. The IFN employed was recombinant IFN-a (12,(160)(161)(162)(163)(164)(167)(168)(169)(170), recombinant IFN-P (171) and lymphoblastoid IFN (165,166), whereas IFN-y had noor only questionable effect (172) ( Table 3). Also patients with T-HCL seemed to respond (173), whereas some rare HCL variants have showed a poor response (82,83).…”
Section: Ifn Treatment Of Hclmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, splenectomy and a interferon Spiegel, 1987;Thompson and Fefer, 1987;Fahey et aI., 1987) were the standard treatment approaches to HCL. The majority of patients on a interferon are known to relapse after stopping therapy (Jaiyesimi et aI.…”
Section: Ifiersmentioning
confidence: 99%
“…After that. an increasing number of patients were treated with alpha-IFN, either recombinant or lymphoblastoid (Flandrin et al, 1987: Quesada et al 1986: Worman et al 1987: Thompson & Fefer. 1987: Pralle et al 1987: Damasio et al 1987Glaspy et al 1987).…”
mentioning
confidence: 99%